ANALYSIS OF LEARNING DIFFICULTIES IN MULTIPLICATION ARITMETIC OPERATIONS ON TUTORING STUDENTS - Karina Putri Pramesti; Febriana Nur Cahyaningrum; Aulia Elvina Paramesti; Cholifah Tur Rosidah; Susi Hermin Rusminati (Media Inovasi Pendidikan dan Publikasi, 2023)
Mathematics is a subject taught at various levels of education that has an important role in advancing human thinking. This type of research is descriptive qualitative research. This qualitative approach was chosen because the researcher thought that by using this approach the researcher could describe the problems studied thoroughly, regarding how the difficulty of learning multiplication arithmetic operations was based on the level of difficulty of the questions. The results of this study on student N showed that the thinking process of students became the subject of research in working on multiplication arithmetic operations questions, in the first question with the concept of constructing additions repeatedly, the results of research on students C showed that the thinking processes of students became research subjects in learning multiplication arithmetic operations sometimes still relying on multiplication notes 1 (one) to 20 (twenty). The results of this study on S students showed the students' thinking processes became the subject of research in working on integer arithmetic operations questions, in the first question with material using the properties of integer arithmetic operations. So good learning is learning that can be meaningful or useful for students.